2022
DOI: 10.1007/s00259-022-05746-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based image reconstruction and post-processing methods in positron emission tomography for low-dose imaging and resolution enhancement

Abstract: Image processing plays a crucial role in maximising diagnostic quality of positron emission tomography (PET) images. Recently, deep learning methods developed across many fields have shown tremendous potential when applied to medical image enhancement, resulting in a rich and rapidly advancing literature surrounding this subject. This review encapsulates methods for integrating deep learning into PET image reconstruction and post-processing for low-dose imaging and resolution enhancement. A brief introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…To train our model we had to overcome the limited availability of high quality training data, a common challenge for the deblurring problem ( 53 ) and so we chose to use simulation. We developed a pipeline based on a Monte-Carlo based PET simulator as it can accurately model the PET acquisition process including physical effects resulting in realistic sinograms ( 29 ) that have the same data distribution as the real PET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To train our model we had to overcome the limited availability of high quality training data, a common challenge for the deblurring problem ( 53 ) and so we chose to use simulation. We developed a pipeline based on a Monte-Carlo based PET simulator as it can accurately model the PET acquisition process including physical effects resulting in realistic sinograms ( 29 ) that have the same data distribution as the real PET.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore consider that the clinical data application was successful in illustrating proof-of-concept that a model trained on Monte-Carlo simulated PET data is applicable on real data. Whereas, generalizability to out-of-distribution data is a common critical limiting factor for deep learning-based image processing ( 53 ), in our case this limitation could in principle be overcome by creating more simulations using the Monte-Carlo pipeline with settings tuned ( 29 , 31 ) to simulate different scanners and reconstructions. Nevertheless, a study of generalization exceeds the scope of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…This dataset contains manual segmentations of different elements within the CMR images, including the myocardium, the LV cavity, and the right ventricle at the end of diastole and the end of systole. The structure of the deep learning model that we have used for segmentation is known as the U-net, which has been used repeatedly for medical image segmentation and resolution enhancement in the literature (Li et al, 2018;Zhou et al, 2018;Ronneberger et al, 2015;Ankenbrand et al, 2021;Pain et al, 2022;Rabbani and Babaei, 2022;Rabbani et al, 2022a). To improve the accuracy of segmentation, as suggested in the literature (Xia and Kulis, 2017), we have used two U-net structures in a sequential manner as depicted in Fig.…”
Section: Deep Learning Segmentationmentioning
confidence: 99%
“…However, no clinical study has demonstrated the value of this software to enhance the quality of low-dose 68 Ga PET images, even though nuclear medicine departments are concerned about this issue. Various other deep learning-based methods have been evaluated for low-dose imaging and resolution enhancement, but none of them are currently validated for clinical use ( 14 ). Denoising techniques for 68 Ga-labeled radiotracers in PET imaging have been explored using both reconstruction-based methods and deep-learning techniques.…”
Section: Introductionmentioning
confidence: 99%